Sulfur dioxide (SO2) vertical column density measurements by Pandora spectrometer over the Canadian oil sands - Fioletov, Vitali E.; McLinden, Chris A.; Cede, Alexander; Davies, Jonathan; Mihele, Cristian; Netcheva, Stoyka; Li, Shao-Meng; O'Brien, Jason (ATMOSPHERIC MEASUREMENT TECHNIQUES, 2016)
Vertical column densities (VCDs) of SO2 retrieved by a Pandora spectral sun photometer at Fort McKay, Alberta, Canada, from 2013 to 2015 were analysed. The Fort McKay site is located in the Canadian oil sands region, approximately 20 km north of two major SO2 sources (upgraders), with total emission of about 45 kt yr(-1). Elevated SO2 VCD values were frequently recorded by the instrument, with the highest values of about 9 Dobson Units (DU; DU = 2.69 x 10(16) molecules cm(-2)). Comparisons with co-located in situ measurements demonstrated that there was a very good correlation between VCDs and surface concentrations in some cases, while in other cases, elevated VCDs did not correspond to high surface concentrations, suggesting the plume was above the ground. Elevated VCDs and surface concentrations were observed when the wind direction was from south to southeast, i.e. from the direction of the two local SO2 sources. The precision of the SO2 measurements, estimated from parallel measurements by two Pandora instruments at Toronto, is 0.17 DU. The total uncertainty of Pandora SO2 VCD, estimated using measurements when the wind direction was away from the sources, is less than 0.26DU (1 sigma). Comparisons with integrated SO2 profiles from concurrent aircraft measurements support these estimates.